Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 17 Medan - Latifa Hanum; Husnarika Febriani; Ulfayani Mayasari (Mu'allim, 2023)
The Disclosure Picking up learning model is a model for creating dynamic understudy learning techniques by self-revelation and self-examination, so that results will be gotten that will keep going quite a while in memory and are not handily forgotten by understudies. The reason for this exploration is to find out how results are impacted by utilizing the Disclosure Picking up learning model. Understudies in class VIII at SMP Negeri 17 Medan. The expression "quantitative exploration" alludes to concentrates on that current information in mathematical structure and utilize factual examination. By administering tests to determine the learning outcomes of students, information collection is completed. The trial class and the control class were the two classes used by experts. Considering the assessment shows that there are contrasts in student learning results. The typical post-test consequences of the exploratory and control classes uncover understudy learning results. The control class's average post-test score was 56.57, while the experimental class's average post-test score was 82.27. The delayed consequences of the ttest test show that the tcount regard is 12.237 and the ttable worth is 1.697 so it shows tcount > ttable then Ha is recognized. It is possible to draw the conclusion that students in class VIII at SMP Negeri 17 Medan benefit from the Discovery Learning learning model.